Myocardial redox state predicts in-hospital clinical outcome after cardiac surgery effects of short-term pre-operative statin treatment. - Antoniades, C; Demosthenous, M; Reilly, S; Margaritis, M; Zhang, M; Antonopoulos, A; Marinou, K; Nahar, K; Jayaram, R; Tousoulis, D; Bakogiannis, C; Sayeed, R; et al. (2012)
OBJECTIVES: The purpose of this study was to evaluate the role of the myocardial redox state in the development of in-hospital complications after cardiac surgery and the effect of statins on the myocardial redox state. BACKGROUND: Statins improve clinical outcome after cardiac surgery, but it is unclear whether they exert their effects by modifying the myocardial redox state. METHODS: We quantified myocardial superoxide anion (O(2)(-)) and peroxynitrite (ONOO(-)) and their enzymatic sources in samples of the right atrial appendage (RAA) from 303 patients undergoing cardiac surgery who were followed up until discharge, and in 42 patients who were randomized to receive 3-day treatment with atorvastatin 40 mg/d or placebo before surgery. The mechanisms by which atorvastatin modifies myocardial redox state were investigated in 26 RAA samples that were exposed to atorvastatin ex vivo. RESULTS: Atrial O(2)(-) (derived mainly from nicotinamide adenine dinucleotide phosphate [NADPH] oxidases) and ONOO(-) were independently associated with increased risk of atrial fibrillation, the need for post-operative inotropic support, and the length of hospital stay. Pre-operative atorvastatin treatment suppressed atrial NADPH oxidase activity and myocardial O(2)(-) and ONOO(-) production. Ex vivo incubation of RAA samples with atorvastatin induced a mevalonate-reversible and Rac1-mediated inhibition of NADPH oxidase. CONCLUSIONS: There is a strong independent association between myocardial O(2)(-)/ONOO(-) and in-hospital complications after cardiac surgery. Both myocardial O(2)(-) and ONOO(-) are reduced by pre-operative statin treatment, through a Rac1-mediated suppression of NADPH oxidase activity. These findings suggest that inhibition of myocardial NADPH oxidases may contribute to the beneficial effect of statins in patients undergoing cardiac surgery. (Effects of Atorvastatin on Endothelial Function, Vascular and Myocardial Redox State in High Cardiovascular Risk Patients; NCT01013103).